Evaluation of Nutritional Status and Anxiety Levels in Patients Applying to the Radiation Oncology Outpatient Clinic during the COVID-19 Pandemic: Turkish Society for Radiation Oncology Group Study (TROD 12:02). (26th November 2022) - Yurut Caloglu, Vuslat; Akmansu, Muge; Yalman, Deniz; Karabulut Gul, Sule; Kocak, Zafer; Arican Alicikus, Zumre; Serarslan, Alparslan; Akyurek, Serap; Zoto Mustafayev, Teuta; Demiroz, Candan; Colpan Oksuz, Didem; Kanyilmaz, Gul; et al.
Abstract: Cancer patients often face malnutrition, which negatively affects their response to cancer treatment. This study aims to analyze the effects of the COVID-19 pandemic on nutritional status and anxiety in cancer patients with different types and stages of cancer. This is a cross-sectional cohort study that includes 1, 252 patients with varying cancer types from 17 radiation oncology centers. The nutritional risk scores (NRS-2002) and coronavirus anxiety scale (CAS) scores of all patients were measured. NRS-2002 ≥ 3 and CAS ≥ 5 were accepted as values at risk. Of all patients, 15.3% had NRS-2002 ≥ 3. Breast cancer was the most prevalent cancer type (24.5%) with the lowest risk of nutrition (4.9%, p  < 0.001). Nutritional risk was significantly higher in patients with gastrointestinal cancer, head and neck cancer, and lung cancer ( p  < 0.005) and in patients with stage IV disease ( p  < 0.001). High anxiety levels (CAS ≥ 5) were significantly related to voluntary avoidance and clinical postponement of hospital visits due to the pandemic ( p  < 0.001), while clinical postponement was particularly frequent among patients with NRS-2002 < 3 ( p  = 0.0021). Fear and anxiety in cancer patients with COVID-19 cause hesitations in visiting hospitals, leading to disrupted primary and nutritional treatments. Thus, nutritional monitoring and treatment monitoring of cancer patients are crucial during and after radiotherapy.